Ranunculus oblitus (section Batrachium, Ranunculaceae), a new species from South America - Wiegleb, Gerhard; Desfayes, Michel; Bobrov, Alexander A. (Phytotaxa, 2022)
Ranunculus oblitus, a new species of Ranunculus section Batrachium, is described from South America. The species is significantly different from the European laminar-leaved species R. aquatilis, and the Holarctic submerged species R. trichophyllus. It resembles the North Asian-North American species R. mongolicus differing by narrower petals, larger and fewer achenes. Available molecular data indicate affiliation to North American taxa of the R. trichophyllus group, especially R. porteri. The species occurs along the west coast of the continent from southern Peru to southern Chile, extending from sea level to an elevation of 4500 m a.s.l. in the Andes. There is some evidence that a second native Batrachium species occurs in South America.